KOMPARASI KITAB-KITAB TAFSIR AL-QUR’AN ERA KLASIK DAN MODERN ATAS TEORI DAN MODEL KOMUNIKASI KELOMPOK UNTUK PENDIDIKAN ANAK PADA QS. LUQMAN/31: 13-19 - Abdul Ghaffar (STAI Masjid Syuhada Yogyakarta, 2021)
Efforts of interpretation by a mufassir cannot be separated from the context of his social space. Because the interpretation process that is done is not in a empty room that is independent of social life. This thing cannot be separated from the effort of an interpreter with the surrounding of social environment. Under these circumstances, it is very fascinating to analyze the interpretation with the currently developing educational nowadays, for instance, knowing the extent to which interpretation embraces the science of child education in the Qur’an. From here, then the question arises, how the interpretation of the classical and modern era of verse Q.S. Lukman / 31: 13-19? How is the compatibility of theories and models of child education delivered by education experts and explanations of classical, modern era commentators on this verse? Looking at the context of this research, the theoretical review used is the theory of group communication, which in this theory said that a group is the minimum that occurs between two people. This theory also states that in communication a group must contain three types; Learning Group, Growth Group, and Problem solving group.